Improving Patient Experiences and Outcomes Through Personal Care Aide Training - Clare C Luz PhD; Katherine V Hanson MS; Yuning Hao MS; Elizabeth Spurgeon MD (Journal of Patient Experience, 2018)
Introduction: The rapidly aging US population is resulting in major challenges including delivering quality care at lower costs in the face of a critical health-care workforce shortage. The movement toward home care has dramatically increased the need for qualified, paid personal care aides (PCAs). Adequate PCA training that focuses on skills for person-centered, at home support is an imperative. This study provides evidence that clients of PCAs who have completed a comprehensive, evidence-based PCA training program, titled Building Training…Building Quality (BTBQ), report higher satisfaction and better health outcomes, compared to clients of PCAs with lesser or other training. Methods: A mixed-methods, quasi-experimental design was used to compare self-reported survey responses from clients of BTBQ-trained PCAs (treatment group) with responses from clients of non-BTBQ-trained PCAs (control group). Results: Clients of BTBQ-trained PCAs had significantly fewer falls and emergency department visits compared to clients whose PCAs had no BTBQ training ( P < .05). Conclusion: BTBQ-like PCA training reduces costly adverse events.